2005
DOI: 10.1097/00000542-200506000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Painful Nerve Injury Decreases Resting Cytosolic Calcium Concentrations in Sensory Neurons of Rats

Abstract: Painful SNL nerve injury depresses resting [Ca]c in sensory neurons. This is most marked in axotomized neurons, especially the large and capsaicin-insensitive neurons presumed to transmit non-nociceptive sensory information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
63
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(75 citation statements)
references
References 57 publications
11
63
1
Order By: Relevance
“…However, the high redox pressure also can cause a large ROS formation (Fig. 4) (97). The decreased basal Ca 2þ level in striatal neurons has been found in experiments on HD knock-in mouse model (98).…”
Section: The Essential In Vivo Role Of the Masmentioning
confidence: 78%
“…However, the high redox pressure also can cause a large ROS formation (Fig. 4) (97). The decreased basal Ca 2þ level in striatal neurons has been found in experiments on HD knock-in mouse model (98).…”
Section: The Essential In Vivo Role Of the Masmentioning
confidence: 78%
“…This offset after the transient has not previously been quantified and indicates a prolonged memory-like residual after activation of sensory neurons. We have previously shown that resting [Ca 2+ ] c is particularly depressed in L5 neurons after SNL, 12 perhaps because of the lack of postactivation offset. The resting [Ca 2+ ] c is regulated by the balanced operation of endoplasmic reticulum Ca 2+ release, plasma membrane Ca 2+ adenosine triphosphatase extrusion, and Ca 2+ influx through channels sensitive to intracellular Ca 2+ stores (storeoperated Ca 2+ channels), 27 indicating effects on these processes specific to injury and neuronal types.…”
Section: Discussionmentioning
confidence: 97%
“…12,19 This segregates neurons into a population of large neurons with predominantly low-threshold receptive field properties and small neurons predominantly responsive to nociceptive stimuli. 20 Because sensitivity to capsaicin is a feature that distinguishes thermal nociceptors, 21 a subset of neurons were further characterized by their response to capsaicin.…”
Section: Analysis and Statisticsmentioning
confidence: 99%
See 2 more Smart Citations